Determination of trace elements and heavy metals in agricultural products cultivated at the Rimac river valley in Lima city using nuclear and related analytical techniques - Bedregal, Patricia (2004)
There are strong indications that the Rimac river valley is being contaminated with heavy metals and an excess of trace elements that come from some industrial and mining activities developed along the Rimac river valley. The agricultural products cultivated there in could be suffering the same effect. Nuclear and related analytical techniques will play an important role in the study of pollution by providing information concerning the degree of contamination in some agricultural products cultivated in the valley and consumed by the population of Lima.